Design and Development of Image Forensic Techniques for Achieving Security in Image Processing - Shekharappa Gouda, Tanush; M Ravishankar, M Ravishankar; H A, Dinesha (Journal of Neonatal Surgery, 2025)
Ensuring authenticity and security has become a critical challenge with the increasing use of digital images in various applications. Image forensics plays a crucial role in detecting tampering, verifying image integrity, and preventing malicious modifications. This research paper focuses on the design and development of image forensic techniques that enhance security in image processing. It explores various approaches, such as passive forensics, active forensics, machine learning-based forensic analysis, and cryptographic techniques for image authentication. The paper also discusses real-world applications, challenges, and future directions in image forensic research. With the increasing reliance on digital images across various domains, ensuring their authenticity and security has become a major challenge. Malicious modifications such as image forgery, deepfake manipulations, and adversarial attacks pose significant threats, leading to misinformation, legal disputes, and cybersecurity risks. Image forensics plays a pivotal role in addressing these concerns by detecting tampering, verifying integrity, and preventing unauthorized modifications. This research paper presents a comprehensive framework for image forensic techniques, focusing on enhancing security in image processing. It explores passive forensics (detecting inconsistencies without prior information), active forensics (embedding security features like watermarks), machine learning-based forensic analysis (leveraging deep learning for tampering detection), and cryptographic methods (ensuring image authentication using hash functions and blockchain).To strengthen digital image security, we propose hybrid AI-based forensic models integrating deep learning with cryptographic techniques. The research also introduces a blockchain-based forensic framework, ensuring immutable storage and verification of image authenticity. Key real-world applications in digital journalism, medical imaging, surveillance, and forensic investigations are discussed, along with emerging challenges and future research directions in image forensics.